Органи державної фіскальної служби України як суб'єкт інформаційних правовідносин - Литвин, Наталія; Lytvyn, N. (ТНЕУ, 2018)
Досліджено субʼєкти інформаційних правовідносин. Окремо розглянуто органи Державної фіскальної служби України як суб’єкт інформаційних правовідносин. Зазначено, що участь суб’єктів владних повноважень в інформаційних правовідносинах має свої особливості, головною з яких є той факт, що основною передумовою для участі такого суб’єкта в інформаційних правовідносинах є його компетенція. The subjects of information legal relations are investigated in the scientific article. The authorities of the State Fiscal Service of Ukraine (next – SFS of Ukraine) as a subject of information legal relations are separately considered. It is noted that the participation of the subjects of power authorities in information legal relations has its peculiarities, the main of which is the fact that the main prerequisite for the participation of such a subject in the information legal relationship is his competence.
Bodies of the State fiscal service of Ukraine as a subject of information legal relations
Keywords: Державна фіскальна служба України; інформація; інформаційні відносини; субʼєкти інформаційних правовідносин; the State Fiscal Service of Ukraine; information; information relations; the subjects of information legal relations